Peningkatan Pengetahuan dan Keterampilan Masyarakat dalam Penanaman Mangrove melalui Sekolah Lapang di Muara Kembang Kalimantan Timur - Maulina Agriandini; Esti Handayani Hardi; Wendrika Wendrika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Muara Kembang is a sub-districts in Muara Jawa District, Kutai Kartanegara Regency, East Kalimantan Province, which borders the coast, so mangrove forests dominate its area. Deforestation of mangrove to be converted into ponds causes a decrease in the area of mangrove forests. Since 2001, the government has intensively rehabilitated mangroves and encouraged communities to plant mangroves independently. Planting mangroves in ponds differs from planting in coastal areas based on planting patterns and plant types. This field school aims to increase coastal communities' understanding of the importance of mangrove ecosystems and increase skills in planting mangroves, especially in active pond areas. The activities were carried out over two days at the Muara Kembang Village Hall. This activity was divided into two stages: lectures by resource people, discussions for the first stage and a mangrove planting simulation for the second stage. The data collection method was through a questionnaire, which was analyzed descriptively before and after training. Based on the results obtained, it can be concluded that the understanding of field school participants has increased regarding the importance of mangrove ecosystems for the aquatic environment, coastal areas, and aquatic animals. Apart from that, participants also know and practice directly how to plant propagules according to the conditions of the surrounding waters. After this training, the participants' knowledge and abilities of mangroves and their planting can be implemented to plant mangroves in ponds.